Mobility and the Role of Education as a Commitment Device - Claudio Thum; Silke Uebelmesser (Center for Economic Studies and ifo Institute (CESifo), 2001)
European integration forces system competition within European countries. This competition has important implications for both the public pay-as-you-go pension scheme and the public education system. Without labor mobility, each generation has an incentive to invest in the human capital of the subsequent generation in order to maximize pension payments. It is a popular belief that increasing labor mobility decreases the incentives to finance the education of the subsequent generation. This paper shows that this is not true if human capital investment increases the mobility of the subsequent generation and can thus be used as a commitment device for low taxes.
Keywords: 330; Education; intergenerational transfers; commitment